Zakład Polityki Gospodarczej - Kalina-Prasznic, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The Division of Economic Policy was established in 1990 to promote high quality, empirically grounded and policy oriented economic research at Wrocław University. The Division’s main goal is to support, enhance and promote research activities of the Faculty and students, and to facilitate sustained discussion of theoretical and economic policy issues of domestic and global importance. The research conducted in the Division is mainly focused on systemic transformation and structural changes of Polish economy. The Division employs 1 titular professor and 5 assistant professors, who provide 18 courses including 6 in English in Bachelor’s and Master’s Programs. The Division organizes conferences, lectures, public seminars, sponsors workshops and promotes collaborative interdisciplinary scholarship, intended to contribute to a broad understanding of economic policy within and outside the academy.
Keywords: Zakład Polityki Gospodarczej; Wydział Prawa Administracji Ekonomii UWr; historia